567. Stigma, Secrecy and Spirituality: An Exploratory Study of How Sociocultural Practices and Perceptions Influence Care Engagement Among HIV-Positive Adults in Akwatia, Ghana. (26th November 2018) - Brown, Kelsey; Deatley, Teresa; Mensah, Gloria; Tucker, Nailah; Flanigan, Timothy; Romero, Maite Alfonso
Abstract: Background: In Ghana, only 65% of HIV-positive adults are linked to HIV care. Stigma, social support and religion influence patients' choice to engage in HIV-related care. This exploratory study examines the relationship between demographic characteristics, perceived stigma, religious service attendance, and participants' adherence to HIV-related appointments. The authors sought to identify characteristics that differed among HIV-positive adults who experienced default in attendance of their HIV clinic appointments compared with those with continuous attendance. Methods: An exploratory study was conducted from June 2017 to July 2017 at St. Dominic's Hospital in Akwatia, Ghana. Structured interviews and medical record reviews were used to collect data on the sociocultural characteristics and appointment adherence of 153 adult HIV-positive participants. Adherence was classified as continuous or noncontinuous. Continuous adherence was defined as attending all scheduled HIV-related appointments over a 6-month period. Only univariate analysis was used to identify characteristics associated with continuous adherence. Results: The mean age was 53, 75% of the participants were female, and 92% identified as Christian. HIV care adherence was continuous among 73% of participants. Seventy-three percent of participants attended religious services more than once per week even though 58% of participants perceived HIV-related stigma from their religious congregation. 77% of participants reported hiding their HIV status from others. The only statistically significant difference between the continuous and noncontinuous groups was with respect to hiding their HIV status from others ( P = 0.054, 90% CI). Conclusion: The sample size ( n = 153) limits the ability to generalize the differences identified between outcome groups. Another limitation is that this study did not examine stigma or disclosure among individuals who had not enrolled in the clinic. Further research is needed to determine whether HIV status concealment can be used as an indicator for patients at higher risk of noncontinuous care engagement. A better understanding of HIV-related stigma, disclosure and how it can be influenced by religious communities and supportive interventions is needed. Disclosures: All authors: No reported disclosures.